Numerical Approach to Processing of Biomechanical Experimental Results - Dumciene, Audrone; Sipaviciene, Saule (Elektronika ir Elektrotechnika, 2016)
The aim is to analyse the possibilities to approximate the data of biomechanical experiments using analytical functions, and to calculate parameters of human limb movement that are of interest to researchers, such as the maximum torque, motion duration, the time taken to achieve maximum torque, motion speed changes during the extension and flexion of limb. The Biodex 3 System Pro was used to collect the experimental data. Right leg extension motion parameters were measured 10 times. The experiment lasted three days, with 1-hour break to rest between tests. The foot extension parameters were: maximum torque 104.38 ± 2.18 Nm, the time to peak torque 436 ± 2.6 ms, motion duration 1000 ± 2.5 ms. The torque values were measured using monitor. It was shown that it is appropriate to use the sixth-order polynomial to approximate the torque versus time curve. Polynomial coefficients with no less 16 significant digits should be used in calculations. Experimental and computational data are presented. DOI: http://dx.doi.org/10.5755/j01.eie.22.5.16342